Inquiry as a Method of Implementing Active Learning - Budi Eko Soetjipto (Universitas Negeri Malang, 2016)
Inquiry teaching is a strategy or teaching methodology designed to meet the needs of children at their own developmental level with their understanding of concepts. It also puts children in charge of their own learning and gives them a sense of responsibility for their learning. Moreover, through inquiry teaching, children will be independent learners with their curiosity to know and explore something with guidance of the teacher. Finally, according to the definition, process and goal of inquiry teaching, it is clear that inquiry teaching can be used to implement active learning methods